Advanced Water Production via Point of Use Super-Ultralow-Pressure Reverse Osmosis and Cellulose-Polyamide Thin-Film Nanocomposite Membranes - Fajardo-Diaz, Juan Luis; Martinez-Iniesta, Armando David; Yamanaka, Ayaka; Tejima, Syogo; Izu, Kazou; Saito, Shigero; Maeda, Jun; Khakani, My Ali El; Wongwiriyapan, Winadda; Wang, Feng; Hayashi, Takuya; Takeuchi, Kenji; et al. (My University, 2025)
A novel thin-film nanocomposite reverse osmosis (RO) membrane was developed for point-of-use applications (POU-RO) at super-ultralow pressure (0.2 MPa), incorporating carboxymethylated cellulose nanofibers (CM-CNF). The CM-CNF with an increased number of oxygen-containing functional groups that positively impacts water flux, salt rejection stability, antifouling characteristics, and resistance to chlorine degradation compared to commercial RO-PA membranes. Transmission electron microscopy (TEM), combined with geodesic and skeletonized image analysis, revealed that the average thickness of the PA/CM-CNF membrane is 1050 nm corresponding to more than four leaf-like layers, significantly higher than commercial membranes, which typically show fewer than two layers. Moreover, a void-free active layer is created, providing excellent substrate coverage. Tests with CaCl2 at 0.2 MPa showed 93.9% salt rejection and a water permeation rate of 0.93 m/d, doubling the performance of commercial membranes. Dynamic simulations confirmed the influence of CM-CNF on enhancing water diffusion at low pressure (0.2 MPa). POU-RO tests, conducted using a 2-inch spiral module fabricated in the laboratory, confirmed the superior performance of the CM-CNF membrane. Indeed, high recovery rates (>60%) and high permeation rates (close to 0.7 m/d) have been achieved by the membranes. This performance is twice than the commercial counterparts tested at 0.2 MPa.
Keywords: carboxymethylated-cellulose nanofibers; chlorine resistance; point of use reverse osmosis; super-ultralow-pressure membranes; thin-film nanocomposite